2011
DOI: 10.1177/0022022111415671
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Adverse Situations Within Exchange Relationships

Abstract: When faced with adverse situations in exchange relationships, the people involved are required to respond. Response strategies are reactions to such adverse situations and represent cognitive schemata organized in an integrated structure forming a mental map. Extant response strategy research implicitly assumes that the content and internal structure of response strategies is universal, but with few exceptions, it fails to assess cross-cultural validity, a necessary step to investigate potential cultural varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
(152 reference statements)
1
12
0
Order By: Relevance
“…Finally, the database of music analyzed was limited to that which had enjoyed popularity in the United Kingdom, such that the present findings cannot speak to music and emotion in other cultures. However, although the findings concerning genre and mood would likely differ cross-culturally, we are optimistic that future research concerning energy and mood in even radically different cultures to those investigated here would yield similar findings, given that Russell (1983) found evidence supporting the circumplex among native speakers of Gujurati, Croatian, Japanese, and Chinese; Russell, Lewicka, and Niit (1989) found evidence confirming the circumplex model among Chinese participants; and Furrer, Tjemkes, Aydinlik, and Adolfs (2012) found similar results in Japan.…”
Section: Discussionsupporting
confidence: 51%
“…Finally, the database of music analyzed was limited to that which had enjoyed popularity in the United Kingdom, such that the present findings cannot speak to music and emotion in other cultures. However, although the findings concerning genre and mood would likely differ cross-culturally, we are optimistic that future research concerning energy and mood in even radically different cultures to those investigated here would yield similar findings, given that Russell (1983) found evidence supporting the circumplex among native speakers of Gujurati, Croatian, Japanese, and Chinese; Russell, Lewicka, and Niit (1989) found evidence confirming the circumplex model among Chinese participants; and Furrer, Tjemkes, Aydinlik, and Adolfs (2012) found similar results in Japan.…”
Section: Discussionsupporting
confidence: 51%
“…The circumplex structure of response strategies Building on the passiveeactive and constructiveedestructive two-dimensional space, Furrer et al (2012) empirically demonstrated that a circumplex structure best represents the interrelationships among response strategies. A circumplex structure organizes response strategies along the circumference of a circle on the basis of the degree of compatibility and incompatibility (Fabrigar et al, 1997).…”
Section: A Model Of Response Strategies In Strategic Alliancesmentioning
confidence: 99%
“…This discrepancy between theory and empirical findings could be attributed to a misconceptualization of response strategies as independent from one another. Furrer et al (2012) thus suggest that response strategies should be conceptualized as a circumplex structure rather than discrete responses. Whereas a circumplex structure, akin to a discrete model, builds on a two-dimensional space, it also stipulates the order of response strategies along the circumference of a circle on the basis of their degree of compatibility (Fabrigar et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Effective influence through leaders -global or otherwise -is characterized by ambiguously complex interrelated relationships, communications, values, missions, motivations, and visions (Gundling, 2003;Kupka & Cathro, 2007;Lee, 2005Lee, , 2009Lee & Sukoco, 2008;Service & Arnott, 2006). This complexity shows when one views the varied constituents commanding attention with their all-too-often mutually exclusive desires (Furrer, Tjemkes, Aydinlik, & Adolfs, 2012;Takeuchi, 2010;Takeuchi, Yun, & Tesluk, 2002). It seems "unconscious processes are better when everything is ambiguous [p. 243]… [Acquire] a set of practical skills that enable [you] to anticipate change" (Brooks, 2011, p. 249).…”
Section: Cross-cultural Leadership For the Rest Of Us (Figures 3 And 5)mentioning
confidence: 99%